A Exploration Factor Analysis, Validity and Reliability Tests of the Self-Transcendence Scale on HIV/AIDS Patients - Niken Wulan Hasthi Murti; Meira Erawati; Nana Rochana (Nurse and Health: Jurnal Keperawatan, 2021)
AbstractBackground: The impact of HIV/AIDS affects the patient's life, both psychologically and physiologically to lower the level of Self-transcendence. So far, the measure to determine the level of self-transcendence in HIV/AIDS patients has not been established in Indonesia. Purpose: The purpose of this study is to conduct a test of the validity and reliability of self-transcendence questionnaires in HIV/AIDS patients. Method: This study was conducted cross-sectionally involving 100 respondents. Data is collected using the purposive sampling method in patients who meet inclusion criteria, namely patients who are undergoing ARV therapy and residing in the Semarang area, and willing to be respondents. Statistical test methods used to test the validity and reliability of questionnaires are person product movement and reliability analysis. Result: The validity and reliability test using SPSS 23 software shows the entire question item has a validity result of >0.164 and the reliability test results show Cronbach's alpha 0.886 result means the entire question item in the Self-transcendence Scale questionnaire is valid and reliable. Conclusion: The results showed that the Self-transcendence scale can be used to measure levels of Self-transcendence in PEOPLE with HIV/AIDS Key Words: Self-transcendence scale, Exploration Factor Analysis validity and reliability test, HIV/AIDS